ҚорақаЛпоғистон Республикасида қорамол чорвачилигининг ривожланиши ва унинг ҳудудий хусусиятлари - Жолдасов, А.С. (SCIENCE and SOCIETY, 2023)
In this article, the development dynamics of cattle breeding in the Republic of Karakalpakstan and issues of its territorial organization are studied.